Intelligent Approach for Improvement of BIPV Systems Performance: Case Study. Issue 10 (February 2019) - Craciunescu, Dan; Fara, Laurentiu; Dabija, Ana-Maria; Sterian, Paul; Fara, Silvian
Abstract: Building-integrated photovoltaics (BIPV) allows incorporating the photovoltaic panels in the roof, windows or facades of buildings in order to increase their energy performance. The authors considered the intelligent MPPT (Maximum Power Point Tracking) method in order to increase the BIPV efficiency for complex urban areas. A BIPV case study is analysed to establish optimize power and conversion efficiency for a residential construction featured by an installed capacity of 30 kW. A numerical modelling developed on MATLAB/Simulink and Excel working environment is introduced; the input data are obtained from Energy Plus software. This approach allows putting in evidence the resulted energy gain using the MPPT algorithm in real conditions for PV panels, especially due to increased shading.